Paleoclimatic interpretation from clay minerals in the early-middle Miocene of southeast Patagonia, Argentina - Matheos, Sergio Daniel; Raigemborn, María Sol; Gómez Peral, Lucia; Tauber, Adan Alejo
The Miocene at the south coast of Santa Cruz province (Argentina) is represented by the transition between the marine sediments of Monte León Formation (late Oligocene - early Miocene) to continental deposits of Santa Cruz Formation (early - middle Miocene). During this time, global warming trends occur that peaked in the Mid- Miocene Climatic Optimum (15 -17 Ma). This period was followed by the late Miocene cooling and drying trend. The upper part of the Monte León Formation (19.3 Ma) is a sedimentary succession composed by fine sandstones, siltstones and tuffs that culminate with conspicuous coquina banks, consisting of shells of Ostrea sp. arranged in life position. This unit reflects the shallowing from a shallow marine environment with neritic and coastal conditions culminating in a paralic environment. The invertebrate fossils of Monte León Formation are related to the first influx of Antarctic waters on to the Argentinean continental shelf, but towards the upper levels an improvement in the climatic conditions is registered. The basal levels of the Santa Cruz Formation, Estancia La Costa Member (~ 16.1-16.5 Ma), is comprised of fine to coarse-size pyroclastic and volcaniclastic deposits reworked by fluvial processes. The fine materials that conforms the floodplain contain immature paleosols (rhizoliths, iron concretions) and bioturbated beds (burrows of bees and scarabeid). The coarser sediments represent sheet-floods deposits of a fluvial system. This unit bears an exceptionally rich fauna of vertebrates that was developed under relatively dry conditions with marked seasonality and open environment (grassland). Compositionally, the upper section of Monte León Formation is represented by lithic sandstones with sporadic glauconitic pellets and reworked vitric tuffs. The more frequent cements are coatings of authigenic clays and carbonate. XRD from clay fraction points to very abundant smectite with minor participation of chlorite, interstratified illite/smectite and illite. On the other hand, the Estancia ...